2353.Distance and Time to Clinic Are Associated with Increased Risk of Detectable HIV-1 Viral Load at a Peripheral Health Center in Rural Western Uganda - Hendren, Cate; Ndizeye, Ronnie; Mumbere, Nobert; Rubinstein, Rebecca J.; Baguma, Emma; Muhindo, Rabbison; Goel, Varun; Ntaro, Moses; Siedner, Mark; Mulogo, Edgar (US: Oxford University Press., 2022)
Antiretroviral therapy (ART) improves the health of people living with HIV (PLHIV) and reduces HIV transmission. While availability and efficacy of ART have improved in sub-Saharan Africa (SSA), access remains a challenge. Travel burden, measured as travel time, distance, and cost, has been posited as a potential barrier to ART. For example, a previous study at a large, urban referral center in Uganda showed GPS-measured distance was associated with clinic absenteeism. However, others suggest that PLHIV are willing to travel farther for HIV care because of stigma or for higher quality care. Less is known about the effect of travel burden in rural settings where transportation infrastructure is sparse, and there are few transportation options. Therefore, the objective of this study funded by the IDSA GERM Program was to explore potential associations between distance- and time-to-clinic in a highland area of rural western Uganda with HIV outcomes including viral suppression.
Keywords: Peripheral Health Center; Distance and Time to Clinic; HIV-1 Viral Load